Exoticism of the East at the 1900 Universal Exhibition in Paris and its echoes - Nashchokina, Maria (project baikal, 2024)
The article considers how the 1900 Universal Exhibition in Paris influenced the appearance of buildings that used images and forms of ancient monuments of India and South-East Asia. The Exhibition made it possible to learn more about the exotic culture of those countries, including the works of architect A. Marcel (Cambodia Pavilion and Panorama ‘Voyage Around the World’). He designed the Baron Empain Palace in Cairo, which reproduces the forms of temples in India and Cambodia. The article studies Russian examples of the use of such forms (Narzan Carbonic Baths in Kislovodsk), as well as the decoration associated with this exotic trend (reliefs of elephants in a guest house in Samara and their sculptures at Samara merchant K. Golovkin’ summer house).